A LONGITUDINAL STUDY ON THE IMPACT OF AN INTEGRATED SEL-CHARACTER EDUCATION CURRICULUM ON PROSOCIAL BEHAVIOR AND MORALITY IN PRIMARY STUDENTS - Ibrahim Kamara; Fatmata Kargbo; Mohamed Bangura (International Journal of Educatio Elementaria and Psychologia, 2025)
The importance of Social-Emotional Learning (SEL) and character education in shaping the behavior and moral development of primary school students has gained significant attention in recent years. However, there is limited longitudinal research examining the sustained impact of integrated SEL-character education curricula on prosocial behavior and moral development. This study investigates the long-term effects of a combined SEL-character education program on prosocial behavior and moral decision-making in primary students. The research aims to assess how such a curriculum influences students’ empathy, cooperation, fairness, and moral reasoning over a period of one academic year. A longitudinal, mixed-methods approach was employed, with quantitative measures assessing prosocial behavior using observational data and surveys, alongside qualitative interviews to capture students’ moral perspectives. The results revealed a significant increase in prosocial behaviors, including improved cooperation and empathy, as well as a noticeable enhancement in moral reasoning among students in the experimental group. These findings indicate that integrating SEL with character education fosters positive behavioral and moral outcomes. The study concludes that a well-structured SEL-character education curriculum is an effective tool for promoting prosocial behavior and moral development in primary students. This research provides valuable insights for educators and policymakers to develop more holistic educational programs that support both the emotional and moral growth of children.